Early diagnostics of acute honestious intestinal incapability with help of X-ray tomography - I. F. Sufiyarov; F. F. Mufazalov; G. R. Yamalova (Сеченовский вестник)
The most important problem determining the indications for surgical treatment of peritoneal adhesion is associated with the uncertainty of the criteria for early diagnosis of intestinal obstruction. Of all the most common acute surgical diseases of the abdominal cavity, acute intestinal obstruction gives the highest lethality. The main reason for this is untimely diagnosis. In two groups of patients, we performed a study of chronic peritoneal peritoneal disease using X-ray computed tomography (RCT), with obstruction (58 patients) and absence of this pathology (56 patients). Analyzing nonparametric statistics with the calculation of the Pearson criterion, with the Yates correction. We presented the criteria for the RCT study, diﬀerential diagnosis of adhesive intestinal obstruction from exacerbation of peritoneal adhesion. The main indicators of this disease: the ﬂuid content in the lumen of the small intestine is more than 200.0 ml, in two or more regions, the inﬂated intestinal loops, an extension of 2.1 mm and more of the intestinal wall. The validity of the diagnostic criteria for RCT research leaves no doubt about the need for their use in preoperative access prognosis and the scope of surgical intervention.